Kajian Sistem Pengolahan Minyak Kelapa Murni (Virgin Coconut Oil) dengan Metode Pemanasan - Zulfadli, Teuku (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Pure coconut oil or Virgin coconut oil is a modification of making coconut oil to produce products with the lower water and acid level , clear and has a long shelf life of 12 months. In terms of economics, pure coconut oil has higher selling price compared to traditional coconut oil by heating coconut milk or precipitating coconut milk in a long time so as to produce rancid odor and poor quality due to high water content and free fatty acid. The purpose of this study was to obtain pure coconut oil with lower water content and free fatty acids according to SNI. There are 3 methods of making pure coconut oil that is method of fermentation, induction and heating, while the method was used in this research is the method of heating. Heating method which is tested by gradual heating or once heating, for gradual warming done preheat with temperature 60-110 ° C with 9 hours of drying and heating time with 60 ° C temperature variations (sample A), 70 ° C (sample B), 80 ° (sample C) and 5 hours, 4 hour and 3 hour drying time. The results showed that drying air temperature had an effect on product quality and length of drying time. The results of the calculation and testing showed the most effective treatment that is on the sample A with water content and free fatty acid content of the lowest reached 0.08% and 0.10%.